Pilot Study: Efficacy of Sensory Integration Therapy for Japanese Children with High‐Functioning Autism Spectrum Disorder. (25th July 2013) - Iwanaga, Ryoichiro; Honda, Sumihisa; Nakane, Hideyuki; Tanaka, Koji; Toeda, Haruka; Tanaka, Goro; Stein, Franklin; Hwang, Eric
Abstract This study's objective was to investigate the efficacy of sensory integration therapy (SIT) for children with high‐functioning autism spectrum disorder (HFASD). The subjects were 20 HFASD children with IQs above 70 selected from previously collected data. Eight participated in individual SIT sessions, and 12 participated in group therapy (GT) including social skill training, communication training, kinetic activities, and child–parent play for 8–10 months. Changes in Total score and five Index scores on the Japanese version of the Miller Assessment for Preschoolers before and after therapy between children in the SIT and GT groups were compared. The results showed that Total score and all Index scores except for Verbal Index increased significantly in the SIT group, while only Total score increased in the GT group. Furthermore, the SIT group showed more improvement compared with the GT group in Total score and on Coordination, Non‐verbal, and Complex Index scores. SIT might have a more positive effect on motor coordination abilities, non‐verbal cognitive abilities, and combined abilities of sensory motor and cognition in children with HFASD when compared with GT. This study has limitations such as being an analysis of previously collected data. Further study should be conducted with a randomized control trial. Copyright © 2013 John Wiley & Sons, Ltd.